Comparative data on different preparation methods of Ru/CeO2 catalysts for catalytic oxidation of chlorine-containing volatile organic compoundsMendeley Data - Pengpeng Cai; Haitao Li; Haibo Zou; Yunkun Pan; Yaoqin Han; Caihe Tang; Yuting Yang; Linghan Xiao; Wei Zheng; Meng Zhou; Jin Li; Mingchun Wu; et al. (Data in Brief)
Under industrial conditions, efficient catalytic oxidation of Chlorinated volatile organic compounds is an important challenge, not only because of the poisonous effect of Chlorinated volatile organic compounds on catalysts, but also because of their high reaction temperature, which has an adverse impact on industrialization. In a recent article (The efficient and stable catalytic combustion of chlorobenzene utilizing a cordierite honeycomb ceramic Ru/CeO2 catalyst: Transitioning from laboratory innovation to practical application) [1], we developed a strategy for preparing a simple and efficient monolithic catalyst for the catalytic combustion of chlorobenzene. Ru/CeO2 was loaded on the industrial support cordierite by a Sol-gel method. Characterization was performed by techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and Brunner-Emmet-Teller(BET) measurements surface area analysis. The Sol-gel method demonstrated superior performance, yielding catalysts with better dispersion, larger surface areas, and consequently, higher catalytic oxidation activity for chlorobenzene, compared to the other two methods. Catalytic tests revealed that the Ru/CeO2 catalyst prepared by the Sol-gel method maintained a 99 % conversion rate of chlorobenzene at 500 °C over 80 h, showcasing remarkable stability and resistance to deactivation. This efficacy is attributed to the enhanced dispersion of Ru and the effective interaction between Ru and CeO2, facilitated by the Sol-gel synthesis process. This method is simple and easy to prepare the catalyst and has broad industrial prospects. The data set is supplemented with XRD, XPS, SEM and SEM-EDS images of the material, providing useful supplementary data; activity evaluation data for dichloromethane, 1,2-chloroethane and chloromethane were measured.